Integrating forest management across the landscape: a three pillar framework. Issue 10 (24th August 2021) - Morgan, Edward A.; Cadman, Tim; Mackey, Brendan
Abstract : Forests are vital ecosystems on a global, regional and local scale, but are under threat from a variety of competing land uses. Integrated landscape approaches have been proposed as a way to create sustainable land use for forests and forest communities through a more integrated, holistic approach to governing resources. A variety of principles for managing landscapes have been proposed as a framework for implementation, but these landscape approaches suffer from a limited theoretical and conceptual basis. This paper seeks to address such shortcomings by identifying and integrating the theoretical components of landscape approaches into a common framework. The paper analyses landscape disciplines, practices and activities and the implementation of common landscape-level principles in the context of forest landscapes to identify the underlying key components. The paper argues that management across a forest landscape must be underpinned by three pillars: ecosystem integrity, strong governance systems and effective planning processes.